Output regulation of linear heterogeneous multi-agent systems - Adib Yaghmaie, Farnaz (2017)
In this thesis, we address output regulation of linear heterogeneous multi-agent systems and use a general model which accounts for heterogeneity of the agents and an arbitrarily finite number of inputs and outputs. We suggest distributed controller design methods for different scenarios. In the first part of this thesis, we study output regulation of a group of linear heterogeneous agents communicating over an acyclic graph. We first show that the output regulation can be achieved through local controller design, then we formulate the output regulation in a graphical game framework. We show that the graphical formulation is robust to multiplicative uncertainties satisfying an upper bound with an infinite gain margin. In the second part of this thesis, we address output regulation of a group of linear heterogeneous agents communicating over a general graph. We derive global and local sufficient conditions for the existence of a distributed controller. We show that our suggested controllers have an H_∞ criterion as a part of their sufficient conditions. We design the controllers based on a set of Linear Matrix Inequalities (LMIs). In the third part of this thesis, we introduce unmodeled disturbances to the multi-agent system and investigate H_∞ output regulation of linear heterogeneous agents communicating over a general cyclic graph. We suggest zero/nonzero-sum multiplayer games and LMI designs for H_∞output regulation. In the fourth part of this thesis, we generalize the idea of classical output regulation to bipartite output regulation. In the bipartite output regulation, the agents communicate over a signed structurally balanced graph and it is desired that the outputs of all agents synchronize in moduli but with different signs. For a structurally balanced signed graph, we prove that the bipartite output regulation is equivalent to the classical output regulation over an unsigned graph whose adjacency matrix is obtained by taking the absolute value of each entry in the adjacency matrix of the signed graph. We obtain a new H_∞ criterion which is sufficient for both the classical output regulation and the bipartite output regulation.